A unique STK4 mutation truncating only the C-terminal SARAH domain results in a mild clinical phenotype despite severe T cell lymphopenia: Case report - Al-Saud, Bandar; Alajlan, Huda; Alruwaili, Hibah; Almoaibed, Latifa; Al-Mazrou, Amer; Ghebeh, Hazem; Al-Alwan, Monther; Alazami, Anas M. (Frontiers in Immunology, 2024)
Mutations in STK4 (MST1) are implicated in a form of autosomal recessive combined immunodeficiency, resulting in recurrent infections (especially Epstein-Barr virus viremia), autoimmunity and cardiac malformations. Here we report a patient with an atypically mild presentation of this disease, initially presenting with severe T cell lymphopenia (< 500 per mm 3 ) and intermittent neutropenia, but now surviving well on immunoglobulins and prophylactic antibacterial treatment. She harbors a unique STK4 mutation that lies further upstream downstream than all others reported to date. Unlike other published cases her mRNA transcript is not vulnerable to nonsense mediated decay (NMD), and yields a truncated protein that is expected to lose only the C-terminal SARAH domain. This domain is critical for autodimerization and autophosphorylation. While exhibiting significant difference from controls, this patient's T cell proliferation defects and susceptibility to apoptosis are not as severe as reported elsewhere. Expression of PD-1 is in line with healthy controls. Similarly, the dysregulation seen in immunophenotyping is not as pronounced as in other published cases. The nature of this mutation, enabling its evasion from NMD, provides a rare glimpse into the clinical and cellular features associated with the absence of a "null" phenotype of this protein.